Nutritional status in relation to oral health status among patients attending dental hospital - Chaloob, Eman K; Qasim, Alhan A (Journal of Baghdad College of Dentistry, 2013)
Background: Good Nutrition is essential for oral and dental health in children. Good eating habits and food preferences are established early in childhood. Oral health problems can effect dietary quality and nutrient intake in another side increase the risk of several systemic diseases., The aim of the present study was to investigate the relation or the effect the of nutritional status in children at age of 5 to16 on the oral health status and dental caries . Materials and Methods: the total sample composed of 153 patients attending the Pedodontic and Preventive Department/College of Dentistry/University of Baghdad, the assessment of nutritional status was performed by using Body Mass Index specific for age and gender according to Chronic Disease and Prevention Center (CDC) growth chart (2000). Ramfjord index teeth were applied to assess oral cleanliness and gingival condition, Dental plaque and Gingival health condition was assessed by using plaque index of Silness and Loe(1964),and gingival index of Loe and Silness( 1963), Calculus index assessment was according to Ramfjord criteria (1959). Dental caries measurement was according to World Health Organization criteria (1997). Results: this study showed no significance in the nutritional status (BMI) of children at 5-16 years of age and plaque index, gingival index, and calculus index, as well as the correlation of significant differences was not found between the nutritional status (BMI) and caries experience. Conclusion: this study reflected that the oral hygiene, gingival health and dental caries were not affected by nutritional status of children at age of 5-16years.